Morning in America : how Ronald Reagan invented the 1980s - Troy, Gil (Politics and society in twentieth-century America., 2005)
Chronicles the political events of the 1980s, offering a year-by-year account of the economic and cultural changes that took place during Ronald Reagan's two terms in the White House.